Video Capsule Endoscopy for Suspected Small Bowel Bleeding in Nepal: Clinical Analysis of Diagnostic Yield and Gastrointestinal Transit Time - Chaurasia, Shivaom; Shrestha, Umid Kumar (Journal of Advances in Internal Medicine, 2025)
BACKGOUND AND AIMS Suspected small bowel bleeding presents a significant diagnostic challenge. Video capsule endoscopy (VCE) has revolutionized small bowel evaluation, yet comprehensive data from South Asia remain limited. This study comprehensively evaluates VCE performance characteristics, diagnostic yield, lesion spectrum, patient safety and procedural factors in a Nepalese population. METHODS Retrospective analysis of 64 consecutive patients undergoing VCE for suspected small bowel bleeding was done at Nepal Mediciti Hospital from June 2021 to July 2024. Data encompassed patient demographics, clinical presentation, VCE findings stratified by Saurin classification, lesion spectrum, procedural parameters, completion rates, retention events, adverse events, and transit time analysis. Statistical analysis performed using descriptive statistics, t-tests and Mann-Whitney U tests. RESULTS Among a total of 64 patients (mean age 58.9 ± 19.0 years; 70.3% male and 29.7% female), diagnostic yield of VCE was 57.8% with predominant finding being angiodysplasia (26.6%), followed by recent bleeding (20.3%), ulcers (9.4%) and polyps (1.6%). High-risk P2 lesions significantly was associated with advanced age (64.7 vs 52.6 years, p=0.018). Capsule completion was 100% (64/64) without any reported adverse events. Mean small bowel transit time (SBTT) was 334.6 ± 80.3 minutes in patients with positive lesions, whereas it was 301.8 ± 79.2 minutes in patients with negative lesions, showing prolonged SBTT in positive patients, with a difference of 32.7 minutes (p=0.110). Orocaecal transit time (OCTT) followed a similar trend with a mean of 363.8 ± 92.1 minutes in positive studies compared to 351.5 ± 132.5 minutes in negative studies (p=0.265). CONCLUSION VCE demonstrates excellent diagnostic yield with good safety profile in Nepalese suspected small bowel bleeding patients. Prolonged SBTT and OCTT were associated with enhanced diagnostic yield. Our study strongly supports VCE as an important diagnostic modality for suspected small bowel bleeding with emerging evidence for gastrointestinal transit time optimization as an adjunctive quality enhancement strategy.